Muslim Spain - Townson, Duncan (London : Cambridge University Press, 1973)
Details that period of Spanish history and civilization when the Muslims invaded and took over the Iberian peninsula, parts of which they controlled for nearly eight hundred years.
Keywords: Muslims -- Spain -- History -- Juvenile literature; Islamic civilization -- Juvenile literature; Middle Ages -- Juvenile literature; Muslims -- Spain; Spain -- Civilization -- 711-1516 -- Juvenile literature; Spain -- Civilization -- 711-1516.